A new method of seawater desalination via acrylic acid based hydrogels: Synthesis, characterisation, and experimental realisation - Höpfner, Johannes (KIT Scientific Publishing, 2014)
The scarcity of potable water is a great challenge. It may be resolved by the desalination of seawater. In this work, the possibilities of a new desalination technique using polymeric hydrogels as a separation medium for water and salt is explored. The bound charges in such a polymeric network prevent salt from entering it - under pressure the desalinated water is released from the gel. It is demonstrated that the method is viable and the influence of various process parameters investigated.